Moment-to-Moment Observation of Parental Media Use and Parent-Child Interaction: Quality and Media Multitasking. (13th August 2022) - Linder, Lisa; McDaniel, Brandon T.; Jaffe, Heather
Abstract : Mobile media proliferation throughout society has infused and complicated environments that formerly were interaction rich (e.g., waiting rooms, restaurants, and playgrounds) with the presence of smart devices. Ethnographic studies have indicated that parental use negatively impacts parent-child interaction quality. The current study reviews and expands on previous research through observing systematically parent-child interaction quality throughout the course of an entire meal (30-140 minutes). Utilizing five-minute intervals, across 93 parent-child dyads, we assessed both within- and between-person moment-to-moment changes in parenting quality (i.e., parental positivity, negativity, and engagement) in the context of parental media use. Between-person, only positivity appeared to decrease when comparing low and high parental media use. Within-person findings indicated that when the parent demonstrated higher than their typical media use, we noted a significant decrease in the quality of engagement and positivity. Differing from ethnographic studies, no change in negativity was identified within-person. Utilizing a lagged interval analysis, we identified a pattern of increased parental engagement with their child following intervals with parental media use, identifying a pattern of parental media multitasking heretofore only observed in ethnographic studies. Implications of findings in the context of previous research and future directions are discussed.